Shopping centres in Poland and Siedlce region - Laskowska, Paulina (Management and Administration Journal, 2023)
The present publication presents concept and essence of a shopping centre as well as location shopping centres in Poland and Siedlce region. In the article there is packaged information which concerns the supply of the surface of trade and characteristics of the Siedlce Gallery. The aim of the article is to show the impact of shopping malls on the society and to present the results of the environmental analysis shopping centre in Siedlce.